1982
DOI: 10.1002/1097-0142(19820515)49:10<2077::aid-cncr2820491020>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization of carcinoembryonic antigen in normal intestine and colon cancer. Abnormal distribution of cea on the surfaces of colon cancer cells

Abstract: The distribution of carcinoembryonic antigen (CEA) in normal small intestine, normal colon, and colon cancer of humans was determined immunocytochemically by the peroxidase-labeled antibody method at the light and electron microscopic levels. In the small intestine, CEA was found in protein synthetic organelles, in the mucus, on the microvilli of goblet cells, and on some microvilli of columnar cells adjacent to goblet cells. In the normal colon, CEA was found in protein synthetic organelles of the fully diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
43
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(51 citation statements)
references
References 38 publications
8
43
0
Order By: Relevance
“…The findings are in concordance with those for CA and CA 50 (Haglund et al, 1986a, b;Ichihara et al, 1988). The sequential change in antigenic distribution from normal epithelium to poorly differentiated and anaplastic carcinomas represents loss of polar distribution of membrane associated antigens, which has been described in various gastrointestinal carcinomas (Ahnen et al, 1982;Nagura et at., 1983;Ichihara et al, 1988) (Ouyang et al, 1987). The expression of CA 242 in normal and neoplastic epithelium of other gast-rointestinal organs is still poorly known.…”
Section: Discussionsupporting
confidence: 85%
“…The findings are in concordance with those for CA and CA 50 (Haglund et al, 1986a, b;Ichihara et al, 1988). The sequential change in antigenic distribution from normal epithelium to poorly differentiated and anaplastic carcinomas represents loss of polar distribution of membrane associated antigens, which has been described in various gastrointestinal carcinomas (Ahnen et al, 1982;Nagura et at., 1983;Ichihara et al, 1988) (Ouyang et al, 1987). The expression of CA 242 in normal and neoplastic epithelium of other gast-rointestinal organs is still poorly known.…”
Section: Discussionsupporting
confidence: 85%
“…Our data therefore illustrate the practicality of characterizing tumours according to a feature heterogeneously expressed in relation to biological behaviour, which represents the outcome of the interrelation and interaction of several clones differeing in this feature. Nevertheless, our study confirms the observations of Ahnen et al (1982) and Hamada et al (1985) in that the pattern of CEA expression closely reflects the degree of differentiation of individual large bowel cancer cells and in addition demonstrates that tumours displaying a rather homogeneous membranous pattern of CEA expression behave aggresively.…”
supporting
confidence: 90%
“…However, there are indications that both the presence of CEA in tissue (Goldenberg et al, 1976) and its localization within the cell (Ahnen, et al, 1982;Hamada et al, 1985) are related to the histological grade of colorectal tumours and thus could be of potential prognostic value.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In malignant epithelium both these structures may hinder passage of antibody molecules. Ahnen et al (1982), demonstrated the localisation of CEA in normal intestine and colon cancer at the ultrastructural level using polyclonal antibodies. The results showed the association of CEA with basement membranes and basolateral surfaces of malignant colonic epithelium in tumours, in contrast to the apical distribution in normal colon, suggesting that the polarity of surface membrane components is disturbed in neoplasia.…”
mentioning
confidence: 99%